Hambani Kahle: re-imagining Avalon Cemetery as a space for social integration - Tarmahomed, Mohammed Hashim (My University, 2021)
This architectural project is a metaphor of the archaeological process of extraction. On a landscape embedded with the layers of displacement, dispossession, erasure and marginalisation, its aim lies in reading the social relations of the site and rewriting a set of spatial relations onto it. The point of conception is Avalon Cemetery, bound by the edges of Soweto, Lenasia and Eldorado Park, the margins where the non-European community of Johannesburg, dissected into Black African, Indian and Coloured, was displaced to, respectively. Not only is this terrain a common space of death, it is also the generator of political agency and cultural presence. In asking the question: ‘How can the relationship between human and landscape be re-imagined through the act of burial in the post-apartheid context?’ a historical inquiry is excavated and evaluated through a theoretical argument, exploring the themes of geography, politics and death, along with their intersections which makes way for the cultural imaginary. This is done by interrogating Johannesburg’s layered relations between terrain and subterrain, unpacking the structures of abjection, surveillance and necropolitics that underlie the South African township together with the cultures that arise from it, marking presence in the landscape. With this reading of place, the architectural intervention re-interprets the spatial expressions of power which act to separate, dispossess and erase, into those that connect, reclaim and reinstate. The site is considered a palimpsest of social relations and the architectural intervention is thus conceptualised as a living archive. The scar separating Black African and Indian spaces becomes a spine that connects them. Its end nodes which lie on a railway line and a desolate tract of land are reclaimed as a railway station, and burial ritual and archives spaces respectively. The built form fuses infrastructure and earth, becoming the stage on which the presence of the erased can be re-inscribed into the landscape
A design project submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) July 2021